2015
DOI: 10.1111/jcpp.12456
|View full text |Cite|
|
Sign up to set email alerts
|

Attention problems in very preterm children from childhood to adulthood: the Bavarian Longitudinal Study

Abstract: Background Very preterm (VP; gestational age <32 weeks) and very low birth weight (VLBW; <1500 grams) is related to attention problems in childhood and adulthood. The stability of these problems into adulthood is not known. Methods The Bavarian Longitudinal Study is a prospective cohort study that followed 260 VP/VLBW and 229 term‐born individuals from birth to adulthood. Data on attention were collected at 6, 8, and 26 years of age, using parent reports, expert behavior observations, and clinical ADHD diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
85
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 40 publications
(67 reference statements)
11
85
0
2
Order By: Relevance
“…For hyperactivity/inattention, scores were persistently higher among the EPT individuals but symptoms decreased slightly over time. The decline in ADHD symptoms and disorders with age for both term born and individuals with very low birth weight has been noted in previous studies which have also shown that the betweengroup difference in ADHD symptoms declines over time [2,30]. We have shown that the group difference in ADHD symptoms (SDQ scores) remains similar over time but the risk for clinically significant problems in EPT individuals declines from childhood to young adulthood.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For hyperactivity/inattention, scores were persistently higher among the EPT individuals but symptoms decreased slightly over time. The decline in ADHD symptoms and disorders with age for both term born and individuals with very low birth weight has been noted in previous studies which have also shown that the betweengroup difference in ADHD symptoms declines over time [2,30]. We have shown that the group difference in ADHD symptoms (SDQ scores) remains similar over time but the risk for clinically significant problems in EPT individuals declines from childhood to young adulthood.…”
Section: Discussionsupporting
confidence: 81%
“…Generally, the greater persistence of problems over time in this study compared with other very and extremely low birth weight cohorts [2,14,16,30,39] may also be related to the greater neurodevelopmental immaturity at birth, higher risk for neonatal brain injury and reduced neurodevelopmental plasticity that is conferred by birth at extremely low gestations compared with birth after 26 weeks of gestation. Indeed, moderate/severe cognitive impairment, an index of such factors [40,41], accounted for some of the difference in the overall behavioral problems with those having cognitive difficulties having persistently greater problems, but did not explain the excess entirely.…”
Section: Discussionmentioning
confidence: 72%
“…Fewer VP/VLBW adults are also married or cohabiting and reproductive rates may be lower than observed in term-born adults 57. Longitudinal studies have also shown that cognitive and behavioural problems in VP/VLBW individuals are more stable over time than in adults born at term 60 68…”
Section: Outcomes In Adulthoodmentioning
confidence: 99%
“…The prevalence of psychiatric symptoms after VP/VLBW birth is significantly higher than that of term‐born individuals (2–4 times increased odds for symptoms in the clinical range compared with the general population) during childhood and adolescence (Johnson & Marlow, , ; Johnson & Wolke, ), and anxiety or mood problems, in particular, may be more prevalent in VP/VLBW adults (Mathewson et al., ; Pyhälä et al., ). VP/VLBW children show increased symptoms of autism spectrum and attention‐deficit/hyperactivity disorders (ADHD) (D'Onofrio et al., ), and ADHD type problems have been shown to continue more often into early adulthood in VP/VLBW than in term controls (Breeman, Jaekel, Baumann, Bartmann, & Wolke, ). In contrast, findings of increased risk for anxiety or mood disorders have been mixed (Johnson & Marlow, ; Johnson & Wolke, ).…”
Section: Introductionmentioning
confidence: 99%